Comparison of endonasal dacryocystorhinostomy (DCR) versus endocanalicular diode laser DCR for the treatment of nasolacrimal duct obstruction - Acar, Mustafa; Gören, Fatih; Yazıcı, Demet; Yıldırım, Güven; San, Turhan (ENT Updates, 2014)
Objective: Dacryocystorhinostomy (DCR), the treatment for nasolacrimal duct obstruction, is generally performed endonasally. In this retrospective study, we compared the anatomical and functional success rate of endonasal DCR with endocanalicular diode laser DCR. Methods: Medical records of 53 patients in endonasal DCR group (Group 1) and 47 in endocanalicular diode laser DCR group (Group 2) were analyzed for preoperative syringing and probing evaluations as well as surgical details, outcomes and complications. Results: Recurrence was observed in eight patients in Group 1 and six in Group 2. Although the recurrence rates differed between the two groups, this difference was not statistically significant (p>0.05). The complications in Group 1 included eight cases of synechia and one tube protrusion, whereas the complications in Group 2 included two cases of synechia, two tube protrusions and two punctum atrophies. The presence of allergy, concha hypertrophy and septum deviation did not significantly increase the rates of recurrence or complications (p>0.05). Bleeding and pain were observed significantly more frequently in Group 1 and the patient comfort was significantly better in Group 2 (p<0.05). Conclusion: Endocanalicular diode laser DCR was found to be a good alternative to endonasal DCR surgery thanks to better postoperative comfort, shorter healing time and less postoperative pain.